2019
DOI: 10.3390/agronomy9100634
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biochars Produced from Dairy Manure at High Pyrolysis Temperatures

Abstract: In this work, the thermochemical analyses of dairy manure (DM), including the proximate analysis, ultimate (elemental) analysis, calorific value, thermogravimetric analysis (TGA), and inorganic elements, were studied to evaluate its potential for producing DM-based char (DMC) with high porosity. The results showed that the biomass should be an available precursor for producing biochar materials based on its high contents of carbon (42.63%) and volatile matter (79.55%). In order to characterize their pore prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…As summarized above, the temperature should be the most important process parameter for determining the pore properties of the biochar products as more pores were generated in severe carbonization conditions. The findings were consistent with those reported by the other feedstocks such as cocoa pod husk [11], rice husk [12], goat manure [21], biogas digestate [33] and dairy manure [34]. The maximal BET surface area of about 300 m 2 /g can be obtained by using these feedstocks in the biochar production when the carbonization temperature reached 800 or 900 • C. In addition, the average pore diameter was obtained from the data on the BET surface area and the total pore volume assuming the pore is of cylindrical and uniform geometry, showing that the pore diameter of the SP-BC-800 product was close to the boundary limit (2.0 nm) between micropores and mesopores.…”
Section: Pore Properties Of Resulting Biocharsupporting
confidence: 91%
“…As summarized above, the temperature should be the most important process parameter for determining the pore properties of the biochar products as more pores were generated in severe carbonization conditions. The findings were consistent with those reported by the other feedstocks such as cocoa pod husk [11], rice husk [12], goat manure [21], biogas digestate [33] and dairy manure [34]. The maximal BET surface area of about 300 m 2 /g can be obtained by using these feedstocks in the biochar production when the carbonization temperature reached 800 or 900 • C. In addition, the average pore diameter was obtained from the data on the BET surface area and the total pore volume assuming the pore is of cylindrical and uniform geometry, showing that the pore diameter of the SP-BC-800 product was close to the boundary limit (2.0 nm) between micropores and mesopores.…”
Section: Pore Properties Of Resulting Biocharsupporting
confidence: 91%
“…In addition, it could be seen from Figure a that the N 2 adsorption capacities of CT600 and CT700 were relatively small, and CT800, CT900, and CT1000 had obvious adsorption hysteresis loops. The occurrence of the adsorption–desorption hysteresis phenomenon suggested that the capillary condensation effect appeared in the absorption process, which was often related to the narrow fissure pores with uniform shape and size of the samples . The results of Figure b and Table also indicated that the average pore diameters of the CT samples were relatively concentrated and uniform and the pores were mostly composed of micropores and smaller mesopores.…”
Section: Resultsmentioning
confidence: 90%
“…As the duration of ball milling approached and exceeded 12 h, Fig. 4(d), 4(e), and 4(f) show that the jatropha seed biochar samples were further reduced in size and developed characteristic agglomerates comprising finer jatropha seed biochar particles attached onto the larger pieces (Tsai et al 2019).…”
Section: Sem Of Biocharmentioning
confidence: 96%